2014
DOI: 10.1016/j.jhydrol.2014.09.082
|View full text |Cite|
|
Sign up to set email alerts
|

SWAT hydrologic model parameter uncertainty and its implications for hydroclimatic projections in snowmelt-dependent watersheds

Abstract: Please cite this article as: Ficklin, D.L., Barnhart, B.L., SWAT hydrologic model parameter uncertainty and its implications for hydroclimatic projections in snowmelt-dependent watersheds, Journal of Hydrology (2014), doi: http://dx. AbstractThe effects of climate change on water resources have been studied extensively throughout the world through the use of hydrologic models coupled with General Circulation Model (GCM) output or climate sensitivity scenarios. This paper examines the effects of hydrologic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…The use of only one snow model is unlikely to be a major source of overall uncertainty, as few catchments in Britain are strongly influenced by snow. Ficklin et al (2014) indicate that uncertainty in snowmelt model parameters can lead to statistically significant differences in hydrological climate change projections. However, Seiller and Anctil (2014) show that, for a catchment in Canada, the snow module is a much smaller source of uncertainty than hydrological model structure, PE formulation and natural variability.…”
Section: Resultsmentioning
confidence: 99%
“…The use of only one snow model is unlikely to be a major source of overall uncertainty, as few catchments in Britain are strongly influenced by snow. Ficklin et al (2014) indicate that uncertainty in snowmelt model parameters can lead to statistically significant differences in hydrological climate change projections. However, Seiller and Anctil (2014) show that, for a catchment in Canada, the snow module is a much smaller source of uncertainty than hydrological model structure, PE formulation and natural variability.…”
Section: Resultsmentioning
confidence: 99%
“…Only if one single forcing dataset is employed, as for example in a flow forecasting system (Candogan Yossef et al, 2011, it may be feasible to estimate the parameters from discharge and/or other data. In addition the current study used one single hydrological model, focusing on parameter and forcing uncertainty and ignoring hydrological model uncertainty, whereas several studies demonstrated that different models may respond differently to (climate) changes in forcing data (Vansteenkiste et al, 2012;Ficklin and Barnhart, 2014). The current study should be repeated with other GHMs to test whether the statement that forcing uncertainty is larger than parameter uncertainty is in general valid.…”
Section: Possibilities For Global Parameter Estimates or Regionalizationmentioning
confidence: 99%
“…SWAT is fully capable of simulating and forecasting surface water parameters and snow melt hydrology parameters on the subcatchment and point scales (Ficklin and Barnhart 2014;Neitsch et al 2011;Arnold et al 2012). Each subcatchment contains the main channel and many hydrologic response units (HRUs), which consist of homogeneous land use/land cover (LULC), soil types and slope.…”
Section: Description Of Swat Modelmentioning
confidence: 99%
“…Each subcatchment contains the main channel and many hydrologic response units (HRUs), which consist of homogeneous land use/land cover (LULC), soil types and slope. Around 2,400 peer-reviewed publications are available related to SWAT model applications, thus the model equations and their theoretical description have been avoided in this research article (Singh et al 2015(Singh et al , 2013Ficklin and Barnhart 2014;Arnold et al 2012;Neitsch et al 2011;Jain et al 2010;Abbaspour et al 2007). The weather generator parameters, such as daily precipitation, daily minimum and maximum temperature, daily humidity, daily wind speed, and daily net solar radiation are necessarily required to set up the SWAT model.…”
Section: Description Of Swat Modelmentioning
confidence: 99%